International Conference of Chemical Engineering & Industrial Biotechnology (ICCEIB 2020) goes virtual - Junaidi, Zakaria (2020)
The 5th International Conference of Chemical Engineering & Industrial Biotechnology (ICCEIB 2020) was successfully conducted virtually on 9-11 August 2020 due to the COVID-19 outbreak. ICCEIB 2020 was organised by the Faculty of Chemical and Process Engineering Technology in collaboration with the City University of Hong Kong, Chulalongkorn University, and Dalian University of Technology.